Heat transfer characteristics of mixed convection in packed beds. (29th June 2022) - Qu, Yuelong; Wang, Liang; Lin, Xipeng; Ling, Haoshu; Bai, Yakai; Zhang, Shuang; Chen, Haisheng
Highlights: The unsteady mixed convective heat transfer process in the packed bed was analyzed. The influence of natural convection on mixed convective heat transfer was revealed. The empirical correlation of forced and mixed convective heat transfer is reported. Abstract: An experimental study on mixed convective heat transfer in a packed bed was carried out. By controlling the temperatures of the fluid and solid and mass flow and flow directions of the fluid, the formation and distribution of the temperature field in the packed bed were analyzed. In addition, the fluid flow and heat transfer process in the fluid–solid system under the coupling effect of natural and forced convection were studied. A modified heat transfer correlation ( N u F = 0.345/ ε · (2 + 1.033 R e h 0.6 P r 1 / 3 ) ) of forced convection in a packed bed was proposed. It was found that natural convection had a significant influence on the overall mixed convective heat transfer. An aiding flow occurred when the fluid with a higher temperature flowed downward in the packed bed, and an opposing flow occurred when the fluid flowed upward. As Ri increased, the strengthening effect of natural convection became more significant. Based on this result, the heat transfer correlation ( N u M 2 = N u F 2 + N u N 2 ) for the mixed convective heat transfer in the packed bed was obtained.